RELATIONSHIPS OF COMPUTED TOMOGRAPHY PARAMETERS OF THE LIQUOR RESTRAIN STRUCTURES OF THE BRAIN WITH ANTHROPOMETRICAL AND SOMATOTYPOLOGICAL INDICES OF YOUNG MEN AND GIRLS OF THE GENERAL GROUPS SUFFERED FROM EPILEPSY - Moskovko, S.P.; Gunas, I.V.; Shevchuk, Yu.G. (World of Medicine and Biology, 2013)
The aim of this research was to study the relations between the computed tomography parameters of the liquor restrain structures of the brain and the anthropometrical indices in young men and girls the patients with epilepsy. The results of the research showed that the young men sick with epilepsy, had more often the multidirectional, with prevalence of direct, reliable relations of medium strength; the girls, sick with epilepsy had the multidirectional, with an identical share of direct and the inverse, reliable relations, only medium strength.